1984
DOI: 10.1080/00032718408065315
|View full text |Cite
|
Sign up to set email alerts
|

Nouveau Modele d'Electrode Modifiee a Base de Carbone et de Polymere

Abstract: A new type of modified électrode is proposed, based on the thermosealing of carbon and a polymer in différent proportions. The mode of préparation and the performances of this new model of polymer électrode are described in détails. The potential range is larger than with other électrodes, particularly in the anodic range. Some performances realized on the behaviour of pharmaceutical compounds are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[17] Nevertheless, during the following years it was claimed that codeine was hardly oxidizable or even devoid of electroactivity, [24,25] which is curious in view of its structure similarity with morphine.…”
Section: Codeinementioning
confidence: 99%
See 1 more Smart Citation
“…[17] Nevertheless, during the following years it was claimed that codeine was hardly oxidizable or even devoid of electroactivity, [24,25] which is curious in view of its structure similarity with morphine.…”
Section: Codeinementioning
confidence: 99%
“…[19] As a result of the apparent difficulty of oxidizing codeine at bare electrodes, in recent years several approaches have been proposed for its quantification using different modified electrodes and a biosensor. [22,25,30,31] All these methods present the advantage of sensitivity (Fig. 5) and selectivity and are demonstrated as a good possibility to be used in routine analysis of codeine Recently, an electroanalytical procedure based on the use of a bare GCE was proposed for the determination of codeine by square wave voltammetry and flow injection analysis.…”
Section: Codeinementioning
confidence: 99%
“…1) from which resulted the formation of a quinonoid type structure [11]. Nevertheless, other studies involving the use of glassy carbon and of modified electrodes showed the appearance of more than one anodic wave that were not identified [12,13].…”
Section: Introductionmentioning
confidence: 89%
“…The carbon polyethylene électrode, which has been earlier reported [6], has found few applications. The kinetics of the reactions are low, but background currents are very low and potential ranges very large, permitting the investigation of drugs not oxidizable at the other solid électrodes [24].…”
Section: Codéine and Menadiol Diacetate A Récent Reportmentioning
confidence: 99%